The Features of English Book Used in 2013 Curriculum at Junior High School Level - Nisrin Darayani; Masduki Masduki (University of Muhammadiyah Malang, 2014)
An Investigation on Team Teaching Implemented by Local and Foreign Teachers in Teaching English at SMAN 1 Ketapang Sampang